2023
DOI: 10.3389/fonc.2023.1154685
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the second-line treatments for patients with small cell lung cancer sensitive to previous platinum-based chemotherapy: A systematic review and Bayesian network analysis

Abstract: ObjectiveIt remains unclear what the best second-line treatment is for patients with small-cell lung cancer sensitive to previous platinum-based chemotherapy.MethodsWe systematically screened randomized controlled trials from several online databases. The primary outcome was objective response rate (ORR), and the secondary outcomes were disease control rate (DCR), overall survival (OS), progression-free survival (PFS), and hematological complications graded 3 to 5. The efficacy of included treatments was ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This finding is consisting with previous reports in patients with smallcell lung cancer, which is classified as NEC according to the World Health Organization (WHO) classification [17]. The nature of NEC and of small-cell lung cancer is considered to be similar, suggesting that second-line platinum and etoposide combination therapy in the present study exhibited shorter PFS and OS compared to first-line therapy, similar to findings in small-cell lung cancer [18].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consisting with previous reports in patients with smallcell lung cancer, which is classified as NEC according to the World Health Organization (WHO) classification [17]. The nature of NEC and of small-cell lung cancer is considered to be similar, suggesting that second-line platinum and etoposide combination therapy in the present study exhibited shorter PFS and OS compared to first-line therapy, similar to findings in small-cell lung cancer [18].…”
Section: Discussionsupporting
confidence: 91%
“…AMR monotherapy has been established as a second‐line chemotherapy regimen in patients with SCLC. 4 A phase‐3 trial evaluating the efficacy of AMR in SCLC reported OS and PFS of 7.5 and 4.1 months, respectively. 10 The most common adverse effect associated with AMR is neutropenia, which can be managed with filgrastim.…”
Section: Discussionmentioning
confidence: 99%
“…Although several ICIs are widely used, and preferred regimens for primary therapy of extensive‐stage SCLC that include ICIs are constantly evolving, the optimal second‐line therapy for SCLC remains unclear. 3 AMR, an inhibitor of DNA topoisomerase II, is considered one of the most effective second‐line agents for SCLC, 4 with some studies reporting the efficacy of second‐line AMR for relapsed SCLC. 5 , 6 Nevertheless, prior to 2023, only two case reports had been published regarding the utilization of AMR for metastatic SCBC.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these two drugs are given one after the other on the same day. The combination of these drugs is highly effective and well tolerated in advanced thymoma, small cell lung cancer, testicular cancer, germ cell tumours [11][12][13]. Cisplatin is classified as an alkylating agent.…”
Section: Introductionmentioning
confidence: 99%